Exporting firm dynamics and productivity growth: Evidence from China - Xiaobing Huang; Xiaolian Liu (Economics: The Open-Access, Open-Assessment E-Journal, 2016)
This paper assesses the productivity growth contributed by the dynamics of exporting firms using firm-level production data of Chinese firms from 2005 to 2009. The authors apply the dynamic Olley-Pakes decomposition with entry and exit proposed by Melitz and Polanec (Dynamic Olley-Pakes Productivity Decomposition with Entry and Exit, 2015), which allows them to decompose the change in aggregate productivity into contributions of surviving firms, entering firms and exiting firms. The study shows that in China, the combined contribution of the three components capturing reallocation amounts to almost half of the change in aggregate productivity. The between-firm market reallocation is found to contribute the most among the three components, followed by the exit of inefficient producers. It also shows that the aggregate productivity growth generated by the dynamics of exporting firms in foreign markets varies according to ownership, location and industry. More specifically, the data suggest that private firms, firms situated in the eastern region of China and firms from high-concentration industries provide a higher contribution to the growth of aggregate productivity.
Keywords: F14; D40; D22; D24; 330; exporting firms; firm dynamics; productivity growth; reallocation effect; China